Thermal property and structural molecular dynamics of organic–inorganic hybrid perovskite 1, 4-butanediammonium tetrachlorocuprate. Issue 57 (21st September 2020) - Yoon, Ma Byong; Lee, Won Jun; Lim, Ae Ran
Abstract : We investigate the thermal behaviour and physical properties of the crystals of the organic inorganic hybrid perovskite [(NH3 )(CH2 )4 (NH3 )]CuCl4 . Abstract : We investigate the thermal behaviour and physical properties of the crystals of the organic inorganic hybrid perovskite [(NH3 )(CH2 )4 (NH3 )]CuCl4 . The compound's thermal stability curve as per thermogravimetric analysis exhibits a stable state up to ∼495 K, while the weight loss observed near 538 K corresponds to partial thermal decomposition. The 1 H nuclear magnetic resonance (NMR) chemical shifts for NH3 change more significantly with temperature than those for CH2, because the organic cation motion is enhanced at both ends of the organic chain. The 13 C NMR chemical shifts for the 'CH2 -1' units of the chain show an anomalous change, and those for 'CH2 -2' (units closer to NH3 ) are shifted sharply. Additionally, the 14 N NMR spectra reflect the changes of local symmetry near T C (=323 K). Moreover, the 13 C T 1ρ values for CH2 -2 are smaller than those for CH2 -1, and the 13 C T 1ρ data curve for CH2 -1 exhibits an anomalous behaviour between 260 and 310 K. These smaller T 1ρ values at lower temperatures indicate that 1 H and 13 C in the organic chains are more flexible at these temperatures. The NH3 group is attached to both ends of the organic chain, and NH3 forms a N–H⋯Cl hydrogen bond with the Cl ion of inorganic CuCl4 . When H and C are located close to the paramagnetic Cu 2+ ion, the T 1ρ value is smaller than when these are located far from the paramagnetic ion.